PENGARUH EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Hanifah, Ulfa (Transpublika Publisher, 2022)
Economic growth in Indonesia is influenced various factors. The purpose of this study is to analyze the effect of exports and imports on economic growth in Indonesia in the period 1987-2020. The data used in this study is secondary data from BPS (Badan Pusat Statistika) and the World Bank 1987-2020. The analytical technique used in this study uses the Error Correction Model (ECM) technique which aims to determine the existence of long-term and short-term relationships that occur in each variable. From the research results, it is know that the exchange rate in the long term and short term, has a negative and significant effect on the rate of economic growth.